Issues of Optimizing the Educational Processes in the Training of Cynologists (Eurasian Journal of Learning and Academic Teaching, 2023)
In this article, scientific-practical recommendations about the factors affecting the efficiency of service activity, professional skills and competencies of cynologists being trained at the National Cynology Center of the Customs Committee, which is part of the law enforcement bodies of the Republic of Uzbekistan, are highlighted.